2020
DOI: 10.1186/s12885-020-07628-0
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of metastasis-associated genes in IDH wild-type glioma

Abstract: Background Glioma is the most common malignant tumor of the brain. The existence of metastatic tumor cells is an important cause of recurrence even after radical glioma resection. Methods Single-cell sequencing data and high-throughput data were downloaded from GEO database and TCGA/CGGA database. By means of PCA and tSNE clustering methods, metastasis-associated genes in glioma were identified. GSEA explored possible biological functions that these metastasis-associated genes may participate in. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Initially reported as an important component of immunological mucosal defences [ 60 ], FCGBP gained more interest recently due to the fact of its variable expression and contradictory roles in different types of malignancies, where it seems to be involved in the immune response associated with cancer development [ 61 , 62 , 63 , 64 ]. Of note, it has been shown to be a metastasis-associated gene in IDH wild-type gliomas [ 65 ] and a tumour antigen in low-grade gliomas [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially reported as an important component of immunological mucosal defences [ 60 ], FCGBP gained more interest recently due to the fact of its variable expression and contradictory roles in different types of malignancies, where it seems to be involved in the immune response associated with cancer development [ 61 , 62 , 63 , 64 ]. Of note, it has been shown to be a metastasis-associated gene in IDH wild-type gliomas [ 65 ] and a tumour antigen in low-grade gliomas [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because protein expression in GBM and META are different, persumely due to the isocitrate dehydrogenase (IDH) state is highly related to glioma tumors. 43,44 If there are sufficient MR data for alleviating the overfitting problem, PRF could also segment lesion regions on the test dataset. However, lesion segmentation is not the main purpose of this study, therefore the lesion segmentation-related parts are described in the supporting information (Table A.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary 3‐T brain tumor experiments showed that CEST frequency importance suggested GBM and META had significant difference at 3.5 and 2.7 ppm, but not at −3.5 ppm. This may be because protein expression in GBM and META are different, persumely due to the isocitrate dehydrogenase (IDH) state is highly related to glioma tumors 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…High-grade malignant tumor tissues are hyperactive and may progress through the steps of the invasion-metastasis cascade within a short period of time ( 103 ). Glioma is an invasive disease that tends to propagate locally and migrate to other parts of the brain ( 104 ). It is increasingly apparent that dysregulation of circRNAs may contribute to the aggressive growth and migration of glioma.…”
Section: Circrnas and Gliomamentioning
confidence: 99%